Positioning and vibration control of a flexible structure in slewing motion by applying Shape Memory Alloys - Janzen, Frederic Conrad [UNESP] (2016)
Flexible structures with slewing motion has been found with increasing frequency in various types of applications, because they are more efficient than their rigid competitors. The study of these systems is important because of the vibrations coming from the mass reduction of structures. Many works have been published presenting control techniques applied in reducing the effects of these vibrations. Several studies demonstrate the application of intelligent materials as actuators for this application. This paper presents a proposal for controlling the angular positioning and vibration of a flexible structure in slewing motion. For such compounds an intelligent actuator materials known as Shape Memory Alloy is employed to control the vibration of the flexible structure. To control the system, the control technique known as State Dependent Ricatti Equation (SDRE), is applied to the control. In order to analyse the dynamics of the system with the proposed control the mathematical modelling of the system is considered and its validation by developed an experimental prototype. Numerical simulations are carried out to analyse the viability of the control and experimental tests are performed in order to validate the theoretical model and the proposed control.